Cellular and metabolic engineering of oleaginous yeast Yarrowia lipolytica for bioconversion of hydrophobic substrates into high‐value products - Soong, Ya‐Hue Valerie; Liu, Na; Yoon, Seongkyu; Lawton, Carl; Xie, Dongming (Engineering in life sciences, 2019)
The non‐conventional oleaginous yeast Yarrowia lipolytica is able to utilize both hydrophilic and hydrophobic carbon sources as substrates and convert them into value‐added bioproducts such as organic acids, extracellular proteins, wax esters, long‐chain diacids, fatty acid ethyl esters, carotenoids and omega‐3 fatty acids. Metabolic pathway analysis and previous research results show that hydrophobic substrates are potentially more preferred by Y. lipolytica than hydrophilic substrates to make high‐value products at higher productivity, titer, rate, and yield. Hence, Y. lipolytica is becoming an efficient and promising biomanufacturing platform due to its capabilities in biosynthesis of extracellular lipases and directly converting the extracellular triacylglycerol oils and fats into high‐value products. It is believed that the cell size and morphology of the Y. lipolytica is related to the cell growth, nutrient uptake, and product formation. Dimorphic Y. lipolytica demonstrates the yeast‐to‐hypha transition in response to the extracellular environments and genetic background. Yeast‐to‐hyphal transition regulating genes, such as YlBEM1, YlMHY1 and YlZNC1 and so forth, have been identified to involve as major transcriptional factors that control morphology transition in Y. lipolytica. The connection of the cell polarization including cell cycle and the dimorphic transition with the cell size and morphology in Y. lipolytica adapting to new growth are reviewed and discussed. This review also summarizes the general and advanced genetic tools that are used to build a Y. lipolytica biomanufacturing platform.